A Conical Beam Antenna Using a Monopole Wire and Rectangular Copper Probe with Four Parasitic Sleeves for UMTS/WLAN Applications - Kanawat Nuangwongsa; Pitchanun Wongsiritorn; Rungsinee Sukkamat; Chuwong Phongcharoenpanich; Tajchai Pumpoung (Journal of Physics Conference Series, 2022)
Abstract This paper aimed to present a wideband monopole antenna for base station applications of indoor reception for UMTS (B1) and WLAN (IEEE 802.11b) systems. The operating frequency was ranged from 1.92 GHz to 2.5 GHz. The proposed antenna was made up of a probe and four connecting parasitic sleeves from the upper copper circular patch to the ground. The rectangular probe structure technique was used to extend the frequency band and effectively improve the matching conditions. The results from simulation and measurement showed that the presented antenna had a proper matching impedance of |S 11 | (dB) lower than -10 dB in the frequency band from 1.71 GHz to 3.72 GHz and also from 1.58 GHz to 2.98 GHz, respectively. The percentage of bandwidth was 74.03% and 61.40%, respectively. The antenna had a conical radiation pattern. The simulated and measured gains were 2.93 dBi to 3.6 dBi and 2.58 dBi to 3.54 dBi, respectively.
Keywords: Antenna Design and Analysis; Energy Harvesting in Wireless Networks; Microwave Engineering and Waveguides